“IMPLEMENTACIÓN DE MECANISMOS PARA EFECTIVIZAR LA REPARACIÓN INTEGRAL A FAVOR DE LA VÍCTIMA POR LOS DAÑOS SUFRIDOS EN EL COMETIMIENTO DEL DELITO - Reyes Troya., Janeth Mireya (2021)
This academic degree dissertation is entitled “Measures’ implementation to make effective the Comprehensive Reparation of Victims that suffered damages in the crime commitment” and the necessity of its execution emerges from the legal study of Código Orgánico Integral Penal, the Ecuadorian penal code, which has been studied and analyzed about the Comprehensive Reparation, primarily around the compensation of material and immaterial damages that the judge determine in favor of the victim in enforceable sentences, nevertheless, even if it is duly recognized by the law, it results to be effective only when the person deprived of liberty has enough properties and money to pay, because in case they do not want to repair immediately, the judge proceeds to order the seizure and auction to the offender’s belongings in order to pay the corresponding values to the victim, but when the person deprived of liberty is without means to make the economical reparation, here begins the difficulty, because the reparation that judge passes on the final judgement cannot be satisfied; it occurs because as the offender is deprived of liberty, it is impossible for him or her to work and generate any economic income. Código Orgánico Integral Penal does not consider the proper procedure to comply the final sentence of the judge in these cases, causing a vulnerable situation to victims and lacking them of the reparation and restitution of the harms caused by the crime, breaking the Effective Judicial Protection and Comprehensive Reparation rights, which are guaranteed through the Republic of Ecuador Constitution and the penal code: Código Orgánico Integral Penal. 5 During the research development there were employed materials and methods, furthermore surveys and interviews were applied to renowned lawyers, the obtained results were useful to establish a legal reform project to Código Orgánico Integral Penal, that includes regulations in compliance with the victims’ rights, concerning measures to make material and immaterial restitution of damages, to finally accomplish Comprehensive Reparation.